Directions In Brazilian Ethnobiology - Ulysses Paulino Albuquerque (Ethnobiology Letters, 2023)
This manuscript examines the prevailing trends within the field of ethnobiology in Brazil and highlights its departure from the traditional dichotomy that partitions ethnobiological inquiry into utilitarian and cognitive perspectives. Instead of an extensive review of the diverse perspectives within the Brazilian ethnobiological landscape, this article primarily highlights the author’s specific viewpoint. As such, this paper outlines some of the orientations and inventive trajectories within the field, emphasizing their origin within the rich academic legacy of Brazil.